Carbon dioxide adsorption in Brazilian coals - José Luciano Soares (2007)
Carbon dioxide (CO2) is one of the most important greenhouse gases. In the period between 1980 and 1998, CO2 emissions increased more than 21% and projections suggest that the emissions will continue to increase globally by 2.2% between 2000 and 2020 and 3.3% in the developed countries. The sequestration of CO2 in deep unminable coal beds is one of the more promising of several methods of geological sequestration that are currently being investigated. CO2 can adsorb onto coal, and there are several studies demonstrating that CO2 dissolves in coals and swells them. At very low pressures (P < 1 bar), CO2 dissolution does not seem to be a problem; however, high pressures are necessary for CO2 sequestration (P > 50 bar). In this study, we evaluated the kinetics and equilibrium of sorption of CO2 on Brazilian coals at low pressures. The adsorption equilibrium isotherm at room temperature (30 degrees C) was measured through the static method. The results showed that the Freundlich model or the Langmuir model is suitable to describe the equilibrium experimental results. The CO2 adsorption capacity of Brazilian coals are in the range of 0.089-0.186 mmol CO2/g, which are typical values for coals with high ash content. The dynamics of adsorption in a fixed-bed column that contains granular coal (particle sizes of 0.8, 2.4, and 4.8 mm) showed that the adsorption rate is fast and a mathematical model was developed to describe the CO2 dynamics of the adsorption in a fixed-bed column. The linear driving force (LDF) was used to describe the rate of adsorption and the mass-transfer constants of the LDF model (K-s) are in the range of 1.0-2.0 min(-1).